Retraction Notice to "Emerging Translational Approaches for Lung Cancer Therapeutics" - Ishpreet Singh Bedi; Pushpendra Jain (Current Cancer Therapy Reviews, 2026)
It has come to the publisher’s attention that an identical version of this article was previously published in the International Journal of All Research Education & Scientific Methods (IJARESM) under the following link: "https://www.ijaresm.com/ uploaded_files/document_file/Jain_Pk_2tsi0.pdf". As duplicate publication violates ethical publishing standards, the publisher has informed the authors and has decided to retract the article from Current Cancer Therapy Reviews. Bentham Science apologizes to the readers of the journal for any inconvenience this may have caused. The Bentham Editorial Policy on Article Withdrawal can be found at https://benthamscience.com/editorial-policies-main.php.